HOMONIM DALAM BAHASA NIAS - Ernimawati Halawa; Mangatur Sinaga; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Homonym is a word, phrase or sentence that has the same form and sound but has a different meaning. The problem that I researched in this study is what are homonyms in Nias language? What are the homonym meaning that contain in Nias language? The aims of this research are to analyze and describe the form and meaning of homonyms in the Nias language which has Gunungsitoli dialect. The method used in this research is descriptive method,a method is used to explain the data that is taken in this researc by using interview, data collection, record, documentation and literature. The application of interview is interviewingor questioning for Nias society in the town of Gunungsitoli were considered to meetcriteria as a sources who understand the language of homonyms in Nias then the result is written down and documentation as collecting the homonym words in Nias language used as research material then analyzed according to the research problem. There are two forms of research results homonym in Nias language, namely 457 that homophones and homonyms homograph and 1homograph homonym but not homophones. In terms of the meaning of homonyms, found 20 homonym meaning, e.g meaning annoyed/angry, understand the meaning, the meaning of the command, meaning informing, meaning conditions, meaning lazy, meaning asked, meaning the ban, meaning the nature, the meaning of work/activity, describe the type of meaning, the meaning of time, meaning size/weight/number, the meaning of the terms, meaning do not like, meaning approved, meaning actors/subjects, meaning surrender, meaning bored and do not understand the meaning. Result of this research shows that the use of homonyms in Nias language community is very high.Key words: Homonyms, Homograph, Homophones, Nias Language